Communication masking in marine mammals: A review and research strategy - Erbe, Christine; Reichmuth, C.; Cunningham, K.; Lucke, Klaus; Dooling, R. (2015)
Underwater noise, whether of natural or anthropogenic origin, has the ability to interfere with the way in which marine mammals receive acoustic signals (i.e., for communication, social interaction, foraging, navigation, etc.). This phenomenon, termed auditory masking, has been well studied in humans and terrestrial vertebrates (in particular birds), but less so in marine mammals. Anthropogenic underwater noise seems to be increasing in parts of the world's oceans and concerns about associated bioacoustic effects, including masking, are growing. In this article, we review our understanding of masking in marine mammals, summarise data on marine mammal hearing as they relate to masking (including audiograms, critical ratios, critical bandwidths, and auditory integration times), discuss masking release processes of receivers (including comodulation masking release and spatial release from masking) and anti-masking strategies of signalers (e.g. Lombard effect), and set a research framework for improved assessment of potential masking in marine mammals.